UNIVERSITY SCHEDULE CONTROL SUBSYSTEM IMPLEMENTATION BASED ON MIXED ARCHITECTURE - ANTONOV, YURIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The schedule analysis on the websites was conducted for more than 60 universities. It has been established that the class schedule is provided to the educational process participants in the form of Excel, Word, PDF files, static and dynamic web pages and a personal cabinet with mandatory authorization. The university schedule management system (Schedule module for Antonov Students Test System) was developed based on the client / server architecture and the architecture of three-level databases. The proposed system consists of such components as SSH Server, A.S.T.S. v3 Database, Schedule Database, Schedule Site and Service, Schedule WebService and Schedule Client. The CAP theorem was used to justify the type of Database Management System. The total number of relational tables in A.S.T.S. v3 Database is over 150. This DB consists of the following components: Core, HRDepartment, Testing, WebGUI, Reports, GradeBook, StudWorks, TimeTableClasses, SocialForm, TransferRestore, EDBO plugins, ScientificDirector, ScientificProfile, Admissions Committee. The Schedule Database consists of two components: Core and TimeTableClasses, and a total has 48 relational tables. The master/slave replication mechanism was used to synchronize data between A.S.T.S. v3 Database and Schedule Database. Access to the A.S.T.S. v3 Database server was implemented using SSH tunnels based on personal keys (RSA or newer). JSON format and Web API can be used for interaction with external systems or services. The higher education institution's schedule management system considered in the work was operated at the Faculty of Mathematics and Information Technologies from 2015 to 2019 academic years and in 2022-2025 in limited mode at the IT Department. Students and teachers have the opportunity to access the current schedule of classes in real time using a browser.
Keywords: relational database; CAP theorem; schedule management; client/server architecture; three-tier database architecture; SSH tunnels